PENGARUH MEDIA PEMBELAJARAN DAN MOTIVASI TERHADAP HASIL BELAJAR MATA KULIAH GEOMETRI RUANG PADA MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA - Y.Y. Dhiki; L. Suryani (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
Government demands the universities as the highest education institution, to compulsory produce quality graduates equipped with good potential and skilful in their respective fields. Thus, the students are expected not only to absorb the course material given, but also are able to apply it creatively. Success or failure of a student in higher education will be influenced by high spirit of life, and strong optimism towards success. Therefore, this study is aimed to investigate the influence of learning media and students’ motivation toward the learning outcome of mathematics education program. Survey is the method chosen for this study with quantitative approach, and 40 students were chosen randomly for solid geometry course in mathematics education program, Universitas Flores. Likert scale was used in the instrument of data collection techniques. Quantitative analysis was used with descriptive statistics, and involved Bivariate (Pearson) Correlation, Classical Assumption Test, and hypothesis testing. The findings show that the learning media (X1) and learning motivation (X2) seen as positive influence on learning outcomes (Y), it can been seen through the correlation analysis from R hiring for X1 against Y for 0.529 and X2 For Y the calculated R value was obtained for 0.732 and the significance value between X1 and X2 for Y abtained two asterisks (**) so that there was positive influence with a significance level of 1%. In other words, the more increase or the better the learning media and students’ motivation are, the more increase and the better the students learning outcome.